Stenotrophomonas, Achromobacter, and Nonmelioid Burkholderia Species: Antimicrobial Resistance and Therapeutic Strategies - Abbott, Iain J.; Peleg, Anton Y. (Seminars in Respiratory and Critical Care Medicine, 2015)
Stenotrophomonas maltophilia, Achromobacter xylosoxidans, and nonmelioid Burkholderia species, namely, Burkholderia cepacia complex, collectively are a group of troublesome nonfermenters. Although not inherently virulent organisms, these environmental Gram negatives can complicate treatment in those who are immunocompromised, critically ill in the intensive care unit and those patients with suppurative lung disease, such as cystic fibrosis. Through a range of intrinsic antimicrobial resistance mechanisms, virulence factors, and the ability to survive in biofilms, these opportunistic pathogens are well suited to persist, both in the environment and the host. Treatment recommendations are hindered by the difficulties in laboratory identification, the lack of reproducibility of antimicrobial susceptibility testing, the lack of clinical breakpoints, and the absence of clinical outcome data. Despite trimethoprim–sulfamethoxazole often being the mainstay of treatment, resistance is widely encountered, and alternative regimens, including combination therapy, are often used. This review will highlight the important aspects and unique challenges that these three nonfermenters pose, and, in the absence of clinical outcome data, our therapeutic recommendations will be based on reported antimicrobial susceptibility and pharmacokinetic/pharmacodynamic profiles.
Keywords: antimicrobial resistance; nonfermenting Gram-negative bacteria; biofilm; cystic fibrosis; immunocompromised patient; intensive care unit; antimicrobial susceptibility testing